EVALUASI KINERJA PENGOLAHAN LIMBAH CAIR RUMAH SAKIT JIWA (RSJ) BANDA ACEH - Putri Nurmala; Suhendrayatna .; Muhammad Zaki (Jurnal Ilmu Kebencanaan : Program Pascasarjana Unsyiah, 2016)
Performance evaluation of liquid waste treatment psychiatric hospitals of Banda Aceh. The management of liquid waste is part of the hospital that serves to protect the public from the dangers of environmental pollution, so it takes a good handling and right through the installation of wastewater treatment (IPAL). This research aims to know the methods of the management and processing of liquid waste conducted by RSJ Banda Aceh, to know the management system and waste liquid waste RSJ Banda Aceh with the Raw quality of the applicable Legislation and regulations and to know the conditions of the environment around the area of RSJ Banda Aceh, before and after the existence of the management of liquid waste. The research sample is liquid waste RSJ Banda Aceh before being processed (inlet), liquid waste after being processed (outlet), drainage and wells. Parameters measured are the BOD (mg/L), COD (mg/L), pH, TSS (mg/L) and temperature (oC) compared to KEPMEN LH No. 58, in 1995 about the raw quality of liquid waste for the activities of the hospital. The analysis of the data used for the determination of the status of the quality of waste water  Pollution Index method (IP) and data analysis using SPSS version 16.0 questionnaire. The results showed that wastewater RSJ Banda Aceh is in the category of light impurities with PIj values of 2.457, so as not to endanger the population around the area of RSJ Banda Aceh.Keywords: Wastewater Management, Wastewater liquid of Hospital, Wastewater Treatment by RSJ Banda Aceh